Internal control over agricultural loans Applied research in the Agricultural Cooperative Bank for the period 2006-2012 - خضير, بشرى فاضل; جريو, زهراء حسين (Journal of Economics and Administrative Sciences, 2016)
AbstractAgricultural Bank is an important source of funding Specialist His role in lending to farmers, it imposes a great job in providing the necessary head for any developmental process in the agricultural sector money. The ACB of ancient Iraqi banks, and that because of its importance to the advancement of the national economy and contribute to the development and regulation of the economic sector through the support and the assignment of the Iraqi agricultural sector in various agricultural activities because it is responsible for the process of granting agricultural loans to farmers bank.The aim of the internal control in the agricultural banks to examine and evaluate the lending policy and politics realizable performance through the use of some of the criteria and indicators that will give a clear concept about the level of performance reached by the bank. The study and evaluation of internal control system in the ACB on a great deal of importance given to the role of the bank in providing services to farmers, which requires subjecting these activities in the bank's internal control system.                                          The research aims to release the importance of internal control and evaluation in the ACB, and evaluate the necessary control over the loans and the efficiency of the recall procedures and the use of resources in agricultural activities. The research has come to the existence of shortcomings in the procedures for granting loans as well as the lack of follow-up for these loans, which means the weakness of private loans and internal control procedures,  which entail a review of some of the internal control procedures.